Upaya Kepala Sekolah Dalam Meningkatkan Mutu Kegiatan Belajar Mengajar di SMK Praja Utama Sribhawono Kecamatan Bandar Sribhawono Kabupaten Lampung Timur Tahun Pelajaran 2023/2024 - Endang Susilowati (Journal of Creative Student Research, 2024)
Education in Indonesia until now, is still running slowly, like an old car running in the middle of traffic flow and on the highway, because education in Indonesia is still plagued by very big problems. The major problems faced by education in Indonesia according to Suparno, SJ include: 1) The quality of education in Indonesia is still low, 2) The learning system in schools is inadequate, 3) The moral crisis that hit Indonesian society. The efforts of the principal of SMK Praja Utama Sribhawono Kec. Bandar Sribhawono Kab. East Lampung in improving the quality of education quite good, because judging from the graduates, alumni of SMK Praja Utama Sribhawono Kec. Bandar Sribhawono Kab. Lampung Timr can compete with graduates from other schools. The location where this research is located is SMK Praja Main Sribhawono, Bandar Sribhawono District, East Lampung Regency. Researchers seek to describe and interpret the principal's efforts in improving the quality of KBM, both in terms of implementation of the principal's efforts, as well as supporting factors and hinder the improvement of KBM quality comprehensive. The general step, the data about the efforts of the head schools in improving the quality of KBM that has been concluded, arranged, explained, then discussed according to the reality that actually in order.